2010
DOI: 10.1007/s11814-010-0257-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanofibers supported Ru catalyst for sorbitol hydrogenolysis to glycols: Effect of calcination

Abstract: Carbon nanofiber (CNFs) supported Ru catalysts for sorbitol hydrogenolysis to ethylene glycol and propylene glycol were prepared by incipient wetness impregnation, calcination and reduction. The effect of calcination on catalyst properties was investigated using thermal gravimetry analysis, temperature-programmed reduction, X-ray diffraction, X-ray photoelectron spectroscopy, transmission electron microscopy and N 2 physisorption. The results indicated that calcination introduced a great amount of surface oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 24 publications
2
38
0
Order By: Relevance
“…A difference in the order of appearance of the epimerisation products was observed for both pentoses. Xylitol was first mainly converted into arabitol (Table 2, entry 12) and subsequently into adonitol ( Table 2, entries [14][15][16][17]. This can on one hand be simply rationalised based on statistics; epimerisation at both C2 and C4 of xylitol yields arabitol, while only epimerisation at C3 can yield adonitol.…”
Section: Isomerisation Reactionsmentioning
confidence: 99%
“…A difference in the order of appearance of the epimerisation products was observed for both pentoses. Xylitol was first mainly converted into arabitol (Table 2, entry 12) and subsequently into adonitol ( Table 2, entries [14][15][16][17]. This can on one hand be simply rationalised based on statistics; epimerisation at both C2 and C4 of xylitol yields arabitol, while only epimerisation at C3 can yield adonitol.…”
Section: Isomerisation Reactionsmentioning
confidence: 99%
“…Others (133)(134)(135)(136)(137) have suggested that the primary use of a base promoter is to prevent leaching of metal particles from the catalyst. Zhao et al confirmed that the base promoter could improve sorbitol hydrogenolysis by neutralizing the organic acids derived from side-reactions (131,132). It is apparent from these studies that NPs are emerging as central catalysts for important reactions relevant to biorenewables transformation.…”
Section: Conversion Of Sugarsmentioning
confidence: 99%
“…Typically, Ru NP catalysts are synthesized and supported on a surface to create a heterogeneous catalyst. The support can be in the form of polymers, silica, carbon, carbon nanofibers (84) or carbon nanotubes (85)(86)(87). Metallic NPs can be synthesized in several ways by utilizing different metal salts, reducing agents and stabilizers.…”
Section: Synthesis Of Metallic Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, conventional hydrogenation catalysts such as Ni, Cu, Ru, and Pt [9−17] based catalysts were mainly used for the sorbitol hydrogenolysis. For example, Zhao et al prepared Ru/CNFs by incipient wetness impregnation for sorbitol hydrogenolysis and the higher activity and selectivity for glycols were obtained compared with Ru supported on commercial activated carbon [14,16]. Banu et al reported that 1,2-propanediol was the major product in sorbitol hydrogenolysis using Ni/NaY as the catalyst, however, when Ni was replaced by Pt, glycerol was presented as the main product in the same process [9,17].…”
Section: Introductionmentioning
confidence: 99%